2022
DOI: 10.1002/hep.32731
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial stress in advanced fibrosis and cirrhosis associated with chronic hepatitis B, chronic hepatitis C, or nonalcoholic steatohepatitis

Abstract: Background & aims: Hepatitis B virus infection causes oxidative stress and alters mitochondria in experimental models. We postulated that HBV might alter liver mitochondria also in human, and the resulting mitochondrial stress might account for the progression of fibrosis in chronic hepatitis B (CHB). Approach & results:The study included 146 treatment-naïve CHB mono-infected patients. Patients with CHB and advanced fibrosis or cirrhosis (F3-F4) were compared to patients with no-mild-moderate fibrosis (F0-F2).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 74 publications
0
19
0
Order By: Relevance
“…Mitochondria are the target of viral attacks, and viral infections have a varying degree of effects on mitochondria 25,26 . To examine the impact of HCMV infection on mitochondrial function, we measured ROS levels 48 h after infection and found that HCMV infection significantly induced ROS production in THP‐1 cells (Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria are the target of viral attacks, and viral infections have a varying degree of effects on mitochondria 25,26 . To examine the impact of HCMV infection on mitochondrial function, we measured ROS levels 48 h after infection and found that HCMV infection significantly induced ROS production in THP‐1 cells (Figure 1c).…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria are the target of viral attacks, and viral infections have a varying degree of effects on mitochondria. 25,26 To examine the impact of HCMV infection on mitochondrial function, we measured ROS levels 48 h after infection and found that HCMV infection significantly induced ROS production in THP-1 cells (Figure 1c). At the same time, mitochondrial membrane potential (ΔΨm), which is important for mitochondrial homeostasis, was decreased after HCMV infection (Figure 1d).…”
Section: Hcmv Infection Caused Mitochondrial Dysfunction and Release ...mentioning
confidence: 99%
“…Recent report has also shown that ROS and lipotoxic intermediates damage mitochondrial DNA, and severe mitochondrial dysfunction further increases ROS production and activates HSC proliferation and dedifferentiation. Therefore, inflammatory cytokines by immune cells may maintain mitochondrial stress and promote fibrosis progression 26 . Hepatocytes are exposed to a high‐oxygen environment due to structural changes in the microvascular system, which is an irreversible lesion of liver fibrosis 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of Hepatology, [9] Loureiro and co-workers present the first comprehensive study that correlates mitochondrial oxidative stress and fibrosis progression in liver samples from a large cohort of 146 treatment-naive chronic hepatitis B (CHB) mono-infected patients, compared with patients with chronic hepatitis C (n = 33), NASH-related cirrhosis (n = 12), and healthy controls (n = 24). A comprehensive study of mtDNA damage and several parameters of mitochondrial dysfunctions was performed and patients with F3-F4 advanced fibrosis (AF) were compared with patients with no/mild (F0-F1) to moderate (F2) fibrosis in each group and between the groups.…”
mentioning
confidence: 99%
“…Leakage of mtDNA and other mito-DAMPs induces both autocrine and paracrine inflammatory responses in neighboring hepatocytes, macrophages, and Kupffer cells and activates HSC to favor the progression of fibrosis. A direct measurement of circulating mtDNA [9] might be informative. The role of these different cell types and inflammatory cells infiltrating the liver should be addressed in patients with different etiologies.…”
mentioning
confidence: 99%